PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PERUSAHAAN - Renadi, Swarga Ditha; Mulyati, Diana Juni; Maruta, IGN Anom (Jurnal Dinamika Administrasi Bisnis, 2017)
This study aims to prove the influence receivables turnover and inventory turnover partially and simultam to company profitability of industrial food and beverage listed on the Bursa Efek Indonesia, as well as proving the most dominant influence of variables receivables turnover and inventory turnover on the profitability of industrial enterprises food and beverage listed in the Bursa Efek Indonesia. This study uses a quantitative approach. Total population in this study are 14 food and beverage industry companies listed on the Bursa Efek Indonesia in 2010. The sampling technique used in this research is purposive sampling. Based on the calculations specified number of samples examined 48 financial report of 9 food and beverage company. The results showed (1) partially, receivables turnover no significant effect on the profitability of the company, while the inventory turnover significantly influence the profitability of food and beverage industry companies listed in Bursa Efek Indonesia 2010-2015. Evident from the test results receivable turnover variable discount a significant value 0.728> 0.05 and 0.351 thitung <ttable 1.67793, while the test result variable inventory turnover significantly discount the value of 0.00 <0.05 and thitung 4451> ttable 1.67793, (2) turnover receivables and inventory turnover simultaneously significant effect on the profitability of the industry food and beverage companies listed in Bursa Efek Indonesia 2010-2015. Evidenced from the results of the second test variable has a value of 10.029 Fhitung of greater value than Ftabelyaitu 3.20, (3) the inventory turnover most dominant influence on the profitability of the industry food and beverage companies listed in Bursa Efek Indonesia 2010-2015. This is evidenced by the final calculation of the value of the rotation, and simultaneous partial test value of inventory turnover have the greatest effect on the profitability of the industry food and beverage companies listed in Bursa Efek Indonesia 2010-2015.Â Keywords: Accounts Receivable Turnover, Inventory Turnover and Profitability (Return On Assets)